Efektivitas Model Pembelajaran Kooperatif Tipe Make A Match terhadap Pemahaman Konsep Penjumlahan Bilangan Cacah Siswa Sekolah Dasar - Mulyadi, erasafira; Nursupiamin, Nursupiamin; Yulia, Yulia (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study aims to determine the differences in mathematics learning outcomes on whole number material between students taught using the Make a Match cooperative learning model and those taught using conventional learning. The method used was a quantitative approach with a quasi-experimental design. The sampling technique employed was total sampling, involving 28 third-grade elementary school students, consisting of 14 students in the experimental class and 14 students in the control class. The research instrument was a 15-item conceptual understanding test that met validity criteria (0.41–0.78) and reliability (Cronbach’s Alpha = 0.87). Data were analyzed using normality tests, homogeneity tests, and an independent samples t-test. The results showed a significant difference between the two groups, with t = 9.170 and Sig. < 0.001. The mean post-test score of the experimental class (86.07) was higher than that of the control class (67.50). In conclusion, the Make a Match cooperative learning model is effective in improving students’ mathematics learning outcomes on whole number material.   Keywords : Conceptual Understanding; Cooperative Learning Model; Learning Outcomes; Make a Match; Whole Numbers